Pola Fungsi Kognitif pada Anak Stunting Usia di bawah 3 Tahun di Kecamatan Padalarang Kabupaten Bandung Barat - Tria Agustia Rahmah; Alya Tursina; Harvi Puspa Wardani (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. The purpose of this study was to determine the correlation between the degree of stunting and the cognitive function of children under 3 years old. This research is an observational analytic study with a cross sectional approach. Sample selection was done through total sampling with 75 stunting children under 3 years old. Data collection used the Capute Scales questionare. The data were analyzed using the chi-square test and the result of the analysis of the correlation between the degree of stunting and cognitive function in children under 3 years old showed a p value=0.00002 and a strong correlation level (R 0.626). There is a significant correlation between the degree of stunting and cognitive function. The impact of stunting can lead to suboptimal child development, resulting in decreased cognitive performance and educational achievement compared to well-nourished children, potentially causing permanent physical and cognitive damage. Abstrak. Tujuan penelitian ini adalah untuk mengetahui hubungan antara derajat stunting dengan fungsi kognitif anak usia di bawah 3 tahun. Jenis penelitian ini adalah analitik observasional dengan pendekatan cross sectional. Pemilihan sampel secara total sampling dengan jumlah subjek 75 anak stunting usia di bawah 3 tahun. Pengambilan data menggunakan kuesioner Capute Scales. Data dianalisis menggunakan uji chi-square, hasil analisis hubungan antara derajat stunting dengan fungsi kognitif pada anak usia dibawah 3 tahun menunjukan p value=0,00002 dan tingkat hubungan yang kuat (R 0,626). Terdapat hubungan yang bermakna antara derajat stunting dengan fungsi kognitif. Pengaruh stunting dapat menyebabkan tumbuh kembang pada anak menjadi tidak optimal, sehingga kinerja kognitif dan prestasi pendidikan menjadi menurun dibandingkan dengan anak-anak yang bergizi baik dan dapat berpotensi menyebabkan kerusakan pada fisik dan kognitif secara permanen.